Transitional woes: On the impact of L2 input continuity from primary to secondary school - Pfenninger, Simone E.; Lendl, Johanna (Studies in Second Language Learning and Teaching, 2017)
In this paper, we discuss the problem of articulation between levels in the educational system, as the transition from a rather more communicative, contentbased and holistic approach to English as a foreign language (EFL) teaching at primary level to more formal and explicit ways of foreign language (FL) teaching at secondary is often experienced as problematic by students and teachers alike (see, e.g., Muñoz, Tragant, & Camuñas, 2015). The results of a mixed methods analysis are presented, in which we analyzed, through a questionnaire and language experience essays, perceived continuity between input received in primary school and secondary school, as well as learners’ beliefs, attitudes and self-efficacy before and after they transitioned to secondary school. Twelve primary schools and six secondary schools in Switzerland participated in the study, with a total of 280 early learners of EFL (biological age 12-13 years, age of onset 8 years). We will argue that one of the main reasons why early FL instruction seems not to bear fruit later in secondary school is that, on the one hand, coherence in curriculum design and practice vary in a few—but crucial—aspects within and between primary schools. On the other hand, the fact that secondary education becomes a meeting point for mixed ability classes also seems to mitigate the potential advantages of an earlier start.